2019
DOI: 10.3389/fimmu.2019.01100
|View full text |Cite
|
Sign up to set email alerts
|

OTUD6B-AS1 Might Be a Novel Regulator of Apoptosis in Systemic Sclerosis

Abstract: Antisense long non-coding RNAs (AS lncRNAs) have increasingly been recognized as important regulators of gene expression and they have been found to play key roles in several diseases. However, very little is known about the role of AS lncRNAs in fibrotic diseases such as systemic sclerosis (SSc). Our recent screening experiments by RNA sequencing showed that ovarian tumor domain containing 6B antisense RNA1 (OTUD6B-AS1) and its sense gene OTUD6B were significantly downregulated in SSc skin biopsies. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 53 publications
(69 reference statements)
0
24
0
Order By: Relevance
“…OTUD6B-AS1 was first reported in systemic sclerosis (10). It is significantly downregulated in systemic sclerosis skin biopsies (10). In the field of cancer research, Wang and colleague reported OTUD6B-AS1 was downregulated in ccRCC tissue samples, and that patients with low OTUD6B-AS1 expression had shorter overall survival than patients with high OTUD6B-AS1 expression, which showed that the different expression levels of OTUD6B-AS1 indirectly correlated with patient survival (11).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…OTUD6B-AS1 was first reported in systemic sclerosis (10). It is significantly downregulated in systemic sclerosis skin biopsies (10). In the field of cancer research, Wang and colleague reported OTUD6B-AS1 was downregulated in ccRCC tissue samples, and that patients with low OTUD6B-AS1 expression had shorter overall survival than patients with high OTUD6B-AS1 expression, which showed that the different expression levels of OTUD6B-AS1 indirectly correlated with patient survival (11).…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of lncRNA expression which acted as oncogenes or tumor-suppressor genes have great significance for the occurrence, development, metastasis, clinical stage and prognosis of thyroid cancer (7)(8)(9). OTUD6B-AS1 was first reported in systemic sclerosis (10). It is significantly downregulated in systemic sclerosis skin biopsies (10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations